Modeling polar marine ecosystem functions guided by bacterial physiological and taxonomic traits - Kim, Hyewon Heather; Bowman, Jeff S.; (.); Steinberg, Deborah K.; Doney, Scott C. (W&M ScholarWorks, 2022)
Heterotrophic marine bacteria utilize organic carbon for growth and biomass synthesis. Thus, their physiological variability is key to the balance between the production and consumption of organic matter and ultimately particle export in the ocean. Here we investigate a potential link between bacterial traits and ecosystem functions in the rapidly warming West Antarctic Peninsula (WAP) region based on a bacteria-oriented ecosystem model. Using a data assimilation scheme, we utilize the observations of bacterial groups with different physiological traits to constrain the group-specific bacterial ecosystem functions in the model. We then examine the association of the modeled bacterial and other key ecosystem functions with eight recurrent modes representative of different bacterial taxonomic traits. Both taxonomic and physiological traits reflect the variability in bacterial carbon demand, net primary production, and particle sinking flux. Numerical experiments under perturbed climate conditions demonstrate a potential shift from low nucleic acid bacteria to high nucleic acid bacteria-dominated communities in the coastal WAP. Our study suggests that bacterial diversity via different taxonomic and physiological traits can guide the modeling of the polar marine ecosystem functions under climate change.